ANALISIS THREE CULTURES OF ANARCHY ALEXANDER WENDT DALAM DINAMIKA HUBUNGAN INDONESIA DAN MALAYSIA - Fasha Pratama; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research aims as a study of constructivist towards Alexander Wendt’s theory about Three Cultures of Anarchy by taking a case study of the relationship between Indonesia and Malaysia. This study tries to apply Alexander Wendt’s theory of Three Cultures of Anarchy in looking at the structure and role or cultures of anarchy in relations between Indonesia and Malaysia through various phenomena and issues. Through this study, the authors found that the dynamics of relations between Indonesia and Malaysia experienced ups and downs where at-first the two countries had a collective identity as shared knowledge which made it easier for the two countries to interact and resolve problems between them. However, the development of representations between them in domestic, regional, and international issues makes this identity irrelevant.This study uses qualitative methods and descriptive analysis with data collection techniques through literature studies from several books, journals, articles, and websites. This study uses a constructivist perspective and the theory and concept of culture developed by Alexander Wendt in understanding international politics through identification of the development of representation, logic, and internalization of culture in a relationship between countries.The results of this study indicate that the representation of each country on the relationship between them is asymmetrical. Indonesia still considers brotherly relations to Malaysia while Malaysia, on the other hand, has little influence on the relationship. They are faced with political, economic, social and cultural development dynamically that have made both Indonesia and Malaysia begin to make preparations facing global competition. This affects the relationship between them in the form of rivalry which is the culture of Lockean Anarchy.Keywords: Three Cultures of Anarchy, Alexander Wendt, Indonesia, Malaysia